Is test specificity the issue in assessing aerobic fitness and performance of runners? A systematic review. - Saddek Benhammou, Laurent Mourot, Filipe M Clemente, Jeremy Coquart, Adel Belkadi (The Journal of Sports Medicine and Physical Fitness, 2024)
Introduction Various tests have been developed to evaluate aerobic fitness and performance of runners. However, a systematic understanding of which methods are more accurate is necessary to provide coaches and the sports sciences community with useful and confident outcomes. This study aims to summarize the evidence regarding the validity, reliability and sensitivity of tests for measuring aerobic fitness and performance in runners of several background of training. Evidence acquisition A systematic search was conducted of Web of Science, PubMed and Scopus up to 31st December 2022 according to PRISMA statement guidelines. Studies that reported findings about tests covering maximal aerobic speed, final velocity achieved during the test, average running speed or other method of evaluating the reference speed during the test were included. We evaluated the risk of bias in the included articles using the Risk of Bias Assessment Tool for Nonrandomized Studies (RoBANS). The tests were categorized into continuous incremental tests, intermittent tests and time-trial test. Evidence synthesis A total of 23 studies met eligibility criteria. These studies contained three background of training: track and road runners (N.=15), trail runners (N.=7) and inexperienced runners (N.=1). Criterion validity was assessed in 73% of the studies, while only 41% of studies examined convergent validity. The majority of the reviewed studies (87%) ignored test-retest reliability. Test sensitivity was not reported in any study. Conclusions At least one aerobic fitness and performance test was identified for each types of background of training. However, some methodological aspects were not provided in the included articles. Most studies examined at least one aspect of validity (i.e., criterion or convergent-related validity), whilst few studies investigated test-retest reliability. Researchers and practitioners can use the information provided in this systematic review to select appropriate tests.
Keywords: Running; Reproducibility of results; Systematic review.